(untitled) (Comprehensive Journal of Science, 2026)
Climate change is a phenomenon that requires attention because it encompasses many aspects. Northwest Libya has witnessed changes in its surface features as a result of climate change. This research aims to study climate change and its impact on human migration, whether temporary, seasonal, or permanent. The research methodology employed a descriptive approach to describe the phenomenon, focusing on the increasing number of migrants of different nationalities and ages. A comparative approach was also used to compare the most densely populated areas and the living conditions available in these areas, which are considered "attraction zones." The research concluded that the poor socioeconomic conditions of migrants drive them to seek areas that provide a means of livelihood. Northwest Libya is considered both a favorable and challenging region for these migrants.